Impact of illumination and encapsulant resistivity on polarization‐type potential‐induced degradation on n‐PERT cells. (12th December 2021) - Habersberger, Brian M.; Hacke, Peter
Abstract: Power loss caused by polarization‐type potential‐induced degradation (PID‐p) in a variety of high‐performance photovoltaic cell types has been observed to be recoverable via subsequent illumination and in some cases preventable via simultaneous illumination. In this report, we describe the results of a study in which the front faces of n‐PERT cells encapsulated in polymers with a broad range of electrical resistivity were exposed to varying and controlled irradiance during PID testing. For a low resistivity ethylene‐vinyl acetate copolymer encapsulant, no reduction in the rate or extent of power loss was observed for irradiance as high as 1, 000 W/m 2, whereas for high and intermediate resistivity polyolefin encapsulants, 100 and 300 W/m 2, respectively, prevented power loss. We introduce a simple model based on charge accumulation that facilitates interpretation of these results whereby degradation via charge accumulation under voltage stress and recovery due to light exposure are opposing and interdependent phenomena that describe the susceptibility of a module to power loss. Abstract : Polarization‐type potential‐induced degradation (PID‐p) has been shown to be recoverable via light exposure; however, the relative rate of this recovery process versus the rate of degradation must be considered to determine if power loss will occur. Here, we report the impact of controlled irradiance and encapsulant resistivity on the rate of PID‐p in n‐PERT cells, demonstrating that low irradiance can prevent power loss with highly resistive encapsulants, while 1‐Sun irradiance fails to prevent power loss with low resistivity encapsulants.